Project-Based Learning Implementation in Vocational Accounting Education: A Case Study at SMK Negeri 1 Klaten - Khasanah, Evanur; Jatmika, Surya (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study investigates the implementation of the Project-Based Learning (PJBL) model in accounting subjects at SMK Negeri 1 Klaten, particularly in the XI AKL class. The background of this research is the need for innovative learning models that enhance students' understanding of accounting through real-world experiences. The purpose of the study is to describe the stages of PjBL implementation and identify the challenges faced by teachers and students. A qualitative descriptive method was employed, with data collected through interviews, observations, and documentation. The findings show that the PjBL model was applied by assigning students to complete accounting cycle projects based on data from local service-based MSMEs. The learning process involved project planning, data collection through field visits, group discussions, and the preparation of financial reports. The model improved students' collaboration, critical thinking, and engagement. However, several obstacles were identified, including students' varying academic abilities, limited prior knowledge of accounting, and issues in group task distribution. It is recommended that future implementation be accompanied by strengthened guidance, differentiated support, and structured evaluation to maximize learning outcomes and prepare students for the professional world.